PERAN ORANG TUA DALAM MEMBANGUN LITERASI DIGITAL MELALUI PENERAPAN METODE STEAM - Muhibbah Suraiya Irham; Erni Munastiwi; Ahmad Syukri Sitorus (Kurikula : Jurnal Pendidikan, 2023)
This study uses the Arikunto PTK Model, namely the role of parents in builing digital literacy trough the application of the steam method. In cycle I, it begins with planning, then carries out the introduction of digital literacy and the application of steam. Research makes observations, then reflection after that improvement. After being corrected in cycle II, it strengthens to check the progress of children’s digital literacy and makes observations again and then makes reflection. In cycle III, strengthening digital literacy and steam application. So the researchers found the results of the classrostoom action research model. In the first cycle, it was 3.2667 (Start Appearing) with an sd value of 0.7988, in the second cycle, 6.2 (Developing as expected) with an sd value of 0.7746, and in the third cycle, obtained 7.6 (developing very well) wih an sd value of 0.5071. This proves that the role of parents in building digital literacy throught steam in early childhood has a significant influence on digital literacy on the application of steam.